Smart speaker as a tool for full inclusion - Sciarretta, Eliseo; Alimenti, Lia (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
They have exotic names like Siri, Alexa and Cortana. They often have a female characterisation (in name and voice) and a consistent virtual personality to be considered family. They have the task of putting themselves at our disposal to try and solve our problems. They have already found a permanent place in our homes. They are the intelligent virtual assistants, i.e. programmes supported by an artificial intelligence that can provide services from commands or questions, which can be given by text but also by voice, and to which they respond with a synthetic voice.